The development and survival but not function of follicular B cells is dependent on IL-7Rα Tyr449 signaling. - Daniel T Patton; Adam W Plumb; Stephen A Redpath; Lisa C Osborne; Georgia Perona-Wright; Ninan Abraham (PLoS ONE, 2014)
IL-7 is a critical cytokine for lymphocyte development. Recent work has highlighted critical roles for IL-7 signaling in mature T cell homeostasis and function, but its role in B cells is less well characterized. Using a knock-in mouse possessing a Tyr to Phe mutation at position 449 (IL-7Rα(449F/449F) mice) within the cytoplasmic SH2-binding motif of IL-7Rα, we evaluated the role of IL-7Rα Y449 motif in spleen B cells. IL-7Rα(449F/449F) mice had reduced numbers and increased death of follicular B cells compared to WT, but had significantly more follicular cells than IL-7Rα(-/-). The death of IL-7Rα(449F/449F) follicular cells was not due to a failure to respond to BAFF or lower levels of BAFF, a critical B cell survival factor. Marginal zone B cells were unaffected by the IL-7Rα(449F/449F) mutation. Any role for TSLP was ruled out, as TSLPR(-/-) mice had an identical B cell phenotype to wild-type mice. Bone marrow chimeras and the absence of IL-7Rα on B cells suggested that IL-7 did not directly regulate mature B cells, but that an IL-7-responsive cell was influencing B cells. IL-7 was also critical at the checkpoint between the T1 and T2 stages in the spleen. IL-7Rα(-/-) mice fail to develop T2 cells, but IL-7Rα(449F/449F) show a reduction compared to WT but not complete absence of T2 cells. We also tested the functional responses of IL-7Rα(449F/449F) to antigens and infection and found no difference in antibody responses to T-dependent or T-independent antigens, or to Influenza/A. IL-7 was important for generation of antibody responses to the intestinal worm H. polygyrus and for naive levels of IgA. Taken together, this suggests that IL-7 regulates follicular B cell numbers and survival in a cell-extrinsic manner, via a bone-marrow derived cell, but is not critical for antibody production outside the gut.